Mobile Information Systems Infrastructure and Design for Adaptivity and Flexibility - Pernici, Barbara (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Mobile devices allow users to access information resources and services over many different distribution channels - anywhere, anytime, anyhow. Technical and usage characteristics of mobile systems are highly variable with respect to user capabilities and context characteristics, therefore an immense level of flexibility is required. Barbara Pernici - with contributions by the research groups involved in the project - presents here a framework for mobile information systems, focussing on quality of service and adaptability at all architectural levels, ranging from adaptive applications to e-services, middleware, and infrastructural elements, as it was developed in the "Multichannel Adaptive Information Systems (MAIS)" project. The design models, methods, and tools developed in the project allow the realization of adaptive mobile information systems in a variety of different architectures. The book is divided into three parts: core technologies for mobile information systems (e.g., adaptive middleware and flexible e-services), enabling technologies (like data management on small devices or adaptive low-power hardware architectures or wireless networks), and methodological aspects of mobile information systems design (such as service profiling or user interface and e-service design for context-aware applications). It provides researchers in academia and industry with a comprehensive vision on innovative aspects which can be used as a basis for the development of new frameworks and applications.